1971
DOI: 10.1139/b71-255
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation and its effects on growth and ion accumulation in tomato plants

Abstract: 1971. Electrical stimulation and its effects on growth and ion accun~ulation in tomato plants. Can. J. Bot. 49: 1809-1815. The effect of small increments of direct current on the growth and ion uptake in Scotia tomato plants was determined. The natural endogenous current in the plant was first assessed and the current applied to reinforce or oppose the natural with three treatment durations per day. Significant increases in linear growth (5 to 30%) were obtained and also significant increases in uptake by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…These results indicated that the applied current may act as a kind of stress. Electric currents have various effects on plant physiology, and seem to promote polar transport of auxins in seedlings (4,9,25) and cultured tissue (11), and ion uptake by tomato plants (2), which in turn affects growth and differentiation. In those reports, the electric currents used were on the order of microamperes.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the applied current may act as a kind of stress. Electric currents have various effects on plant physiology, and seem to promote polar transport of auxins in seedlings (4,9,25) and cultured tissue (11), and ion uptake by tomato plants (2), which in turn affects growth and differentiation. In those reports, the electric currents used were on the order of microamperes.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the uptake rates of macroelements such as N, P, Ca, and Mg were affected by an externally applied electric field (Murr, 1965;Murr, 1966). Black et al (1971) reported an increased absorption A B…”
Section: Xwulhqw 8swdnhmentioning
confidence: 94%
“…Similarly, cations are likely to be attracted toward the negative electric field formed by air anions. The increased cations, including K + , could expand guard cells in leaf epidermal tissues and subsequently open the stomata (Black et al, 1971;Robinson, 1985). However, further studies are required to understand the underlying mechanism.…”
Section: *Dv ([Fkdqjh Lq Doh /Hdyhvmentioning
confidence: 99%
“…In the presence of an EF, chemio-osmotic modifications of ion transport (an equivalent of salt influx or salt efflux driven at the expense of an equivalent of electrogenic proton efflux) could occur in roots (Robinson 1985). Furthermore, the increased ion accumulation seems not to be merely a passive movement under the applied potential, and it is thought that small currents could stimulate or inhibit active ion pumps or alter the internal distribution of growth-regulating compounds (Black et al 1971, Robinson 1985). An interesting observation could be related to another hypothesis: the root orientation in the growing medium.…”
Section: Resultsmentioning
confidence: 99%